Supply Chain Risk Analysis on Vending Machine Products (Study Case in XYZ Company) - Puti Sinansari; Nugroho Priyo Negoro; Muhammad Muadz Abdillah (Jurnal Sosial Humaniora, 2021)
The development of business and technology ecosystems demandsindustry to always make adjustments. Supply chain changes becomeone that is certain to happen. This change process allows thecompany to manage and minimize risks. Therefore, it is necessary toapply good risk management to minimize the impact of risk. As oneof the vending machine service companies in Indonesia, PT XYZ hasa long supply chain, covering the production process, assembling,shipping and customer service. This research aims to identify riskevents and risk agents and determine the priority of risk agents in thevending machine service company at PT XYZ. The design of thisresearch uses the first stage House of Risk method to identify riskevents and risk agents as wellas determining the highest risk agent.Then the highest risk agent is ranked inPareto diagram to determinerisk agent priority. The prospect of this researchwill be an overviewof the risks that may arise in the vending machine servicecompany inIndonesia.